Т. 1. Документы о революционной деятельности и судебном процессе - Брегман А. А.; Федосеева Е. П.; Нечкина М. В. Милица Васильевна; Домашенко Н.; Нератова Н. П.; Пушкин А. С. Александр Сергеевич (1980, 1980)
Авт. указан на корешке